POTENSI IRADIASI GAMMA (CESIUM-137) TERHADAP PERTUMBUHAN TANAMAN BUNCIS (PHASEOLUS VULGARIS L.) - Juliana, Juliana; Hernawati, Hernawati; Rani, Sefrilita Risqi Adikaning Rani; Rahmaniah, Rahmaniah (JOURNAL ONLINE OF PHYSICS, 2024)
This study investigates the effects of gamma radiation from Cesium-137 on the growth of bean plants (Phaseolus vulgaris L.) to understand its impact on plant quality. The Cesium-137 source was applied at a constant distance of 200 cm from the wall, using dose variations of 0 (control), 25 mGy, 50 mGy, 75 mGy, 100 mGy, and 125 mGy. The seeds used in this research were sourced from the Arango bean plantation in Arabika Village, Sinjai Barat District. A descriptive statistical analysis method was employed, presenting the data in tables that were then converted into graphs to illustrate the germination time (in days), stem height (cm), leaf width (cm), and leaf count (number of leaves). The results revealed that sample D, exposed to a radiation dose of 75 mGy, took only 5 days to germinate, with an average stem height of 45 cm, leaf width of 10.6 cm, leaf count of 16 leaves, and an average fruit mass of 0.008 kg. In contrast, the normal germination time for bean plants is 7 days, with a stem height of approximately 30 cm, leaf width of 6 cm, leaf count of 14 leaves, and a fruit mass of 0.006 kg. However, it was observed that both excessively low and high radiation doses could hinder the growth of bean plants.